«¿The money cures every injury? I don’t think so» Reflections about moral damage - Linares Avilez, Daniel (2017)
A situation that has been generated several confusions is the inclusion of person damage next to moral damage in the Civil Code of 1984, both in the national doctrine and judicial decisions.The Author analyses the problems arising from non-property damages in the Peruvian legal system, giving a brief description of its arrival to our Legislation and noting the major directions Doctrine has taken. He focuses on the old and new challenges Judges have on this matter and elaborates a list of considerations to positions seated on the Peruvian Civil Procedure.